(untitled) (Proceedings of the International Conference on Gender and Sexuality, 2023)
Despite the political freedom gained in 1994, black women labour tenants in South African still never tasted the fruits of democracy and live under very harsh conditions and face discriminations. However, such circumstances are seldomly reported in academic literature. Therefore, this paper investigates the challenges faced by women on farms in rural areas using a qualitative exploratory case study design. Primary data from 37 farmers in UMgungundlovu; was derived from the Qina-Mbokodo project case study to investigate barriers to women’s participation in agriculture and support from the government. The results of the analysis identified five themes that embody the difficulties faced by women in farms of uMgungundlovu. These include a lack of community engagement in the Integrated Development Plan (IDP) and District Development Model (DDM), gaps in awareness and knowledge, gender issues, economic empowerment and development, and lack of Technical support. The paper suggests economic empowerment regardless of gaps to help beneficiaries address poverty, as well as social support, participation in integrated development plans, and district development model to address beneficiaries’ low economic status.